Outdoor environment management through air enthalpy analysis - Campos, Firmo Sousa [UNESP]; Sarnighausen, Valéria Cristina Rodrigues [UNESP]; dos Santos Riccardi, Carla [UNESP] (Springer Nature, 2019)
With the ever-progressing urbanization of human society comes lingering public issues, primarily those related to human health and the need to provide environments where the population can be routinely frequent. Also, the effects of climatic changes tend to aggravate such public health issues, mainly respiratory and cardiac symptoms. As such, analyzing and studying those environments can be crucial for public administrations in the decision-making processes. One such method of analysis involves using an air enthalpy index to profile and provide a picture of stress situations, helping expedite preventive measures and hospital logistics. With that, this study used the enthalpy index as a tool to create a picture of the effect of seasonality on chronic health issues, such as respiratory and cardiac symptoms, for the city of Botucatu, a city with a characteristic tropical altitude climate. It was possible to determine that the air enthalpy profile is consistent throughout the year near the estimated thermal comfort boundaries, with peaks outside in hotter months. The hospitalizations tend to be more numerous during the transition from hot to cold seasons. Simple correlation analysis, along with a t test, provided further insight into the issue, showing strong correlation for pneumonia with the maximum enthalpy variation, which can relate to the heat amount variation in a given location. Also, an agreement was observed between enthalpy and an established thermal sensation index, the heat index, meaning that air enthalpy can be a reliable and simple index for environmental thermal comfort analysis. That being said, further studies are necessary to confirm these findings, considering a longer time frame, more diverse hospitalization data, and other meteorological parameters, like wind speed and precipitation.
Keywords: Air enthalpy; Diseases; Human biometeorology; Preventive measurements; Thermal comfort